2022
DOI: 10.1155/2022/4775595
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Estimation of Biomechanical Constitutive Parameters of Passive Porcine Sclera Soft Tissue

Abstract: This study assesses the modelling capabilities of four constitutive hyperelastic material models to fit the experimental data of the porcine sclera soft tissue. It further estimates the material parameters and discusses their applicability to a finite element model by examining the statistical dispersion measured through the standard deviation. Fifteen sclera tissues were harvested from porcine’ slaughtered at an abattoir and were subjected to equi-biaxial testing. The results show that all the four material m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“… 40 , 42 In addition, some studies have identified a preferential orientation of scleral collagen fibers. 54 , 55 The equatorial orientation (measured here) has been reported to be stiffer than the meridional orientation estimated in scleral tissue by biaxial mechanical testing 56 and by OCE (Villegas L, et al; unpublished data; 2023). Certainly, tensile tests should be complemented with new techniques which allow quantification of mechanical properties in several directions simultaneously and avoid destruction of the ocular tissue.…”
Section: Discussionmentioning
confidence: 50%
“… 40 , 42 In addition, some studies have identified a preferential orientation of scleral collagen fibers. 54 , 55 The equatorial orientation (measured here) has been reported to be stiffer than the meridional orientation estimated in scleral tissue by biaxial mechanical testing 56 and by OCE (Villegas L, et al; unpublished data; 2023). Certainly, tensile tests should be complemented with new techniques which allow quantification of mechanical properties in several directions simultaneously and avoid destruction of the ocular tissue.…”
Section: Discussionmentioning
confidence: 50%
“…The tensile tester was operated in displacement control at a uniform strain rate of 0.025/second. Saline 0.91% w/v of NaCl was heated to 33 °C before the sample tissue is placed in the bath for mechanical testing (Ndlovu et al, 2020;Lebea et al, 2021;Ndlovu et al, 2021). A 0.005 N equi-biaxial preload was applied to both longitudinal and circumferential directions.…”
Section: Biaxial Mechanical Testingmentioning
confidence: 99%